The use of cell culture technique in small molecule antidiabetes drug discovery - Bakhtiar, M. Taher (2019)
Type 2 diabetes is a metabolic disorder characterized by insulin resistance caused by multifactorial etiology including environmental factors particularly diet and genetic components. According to International Diabetes Federation in 2017, approximately 425 million adults were suffering with diabetes and it will increase to 629 million in 2045. As part of UN Sustainable Development Goal on Good Health and Well-being, research initiative on the exploration of potential antidiabetes agent from nature has been conducted extensively. Cell culture has been developed as an important tool in antidiabetes drug discovery. The cell culture technique is considered as the most reliable technique to minimize the use of animal in diabetes experimental works under 3R (reduction, replacement and refinement) rules. Recently, most research on diabetes has focused on adipocyte, which is used as a model for testing of adipocyte differentiation, glucose uptake, glucose transport and insulin sensitivity of novel antidiabetes drugs. Numbers of plants and compound have been evaluated for their antidiabetes effects on 3T3-L1 adipocytes cells. It was found that some extracts and compound exhibited interesting antidiabetes properties.